2015
DOI: 10.1589/jpts.27.3171
|View full text |Cite
|
Sign up to set email alerts
|

Electromyography comparison of normal chair-desk system and assistant chair-desk system on fatigue

Abstract: [Purpose] This study was designed to test the effects of the Assistant Chair-Desk System (ACDS), which can reduce the forward tilt of the neck and trunk and the level of fatigue during long lasting study in the sitting position. [Subjects] Fourteen middle school students and 14 college students of mixed gender participated in this study. [Methods] Fatigue level, the trapezius muscle, and the forward tilt angle of the head and trunk as well as distance factors were assessed before after using a normal chair-des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…Previous studies have addressed the influence of body posture and seat characteristics on muscle activity 1 , 11 , 12 ) . The study by Kamil and Dawal 13 ) demonstrated that there is a correlation between postural angle (trunk and pelvic angles) and the activity of the erector spinae, multifidus and cervical erector spinae muscles.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have addressed the influence of body posture and seat characteristics on muscle activity 1 , 11 , 12 ) . The study by Kamil and Dawal 13 ) demonstrated that there is a correlation between postural angle (trunk and pelvic angles) and the activity of the erector spinae, multifidus and cervical erector spinae muscles.…”
Section: Introductionmentioning
confidence: 99%